PENINGKATAN KOMPETENSI GURU MELALUI PELAKSANAAN KKG (KELOMPOK KERJA GURU) DI SMP NEGERI 6 DUMAI - Leni Suryani (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This article reports the teachers’ low competency at SMP Negeri 6 Dumai. Furthermore, it requires action to overcome this problem through the implementation of the Teacher Working Group (KKG). The research described in this article aims to improve the teachers’ competency at SMP Negeri 6 Dumai through the Teacher Working Group. The type of research is school action research (PTS), which aims to find out the improvement of teachers’ competency in teaching through the implementation of the KKG (Teacher Working Group) at SMP Negeri 4 Dumai. The results of the implementation of the KKG presented by the tutor found that from Cycle I it increased in Cycle II. It achieved a percentage score of 75% in Cycle I, then it increased to 95% in Cylce I. In the educational aspect, in Cycle I it was 58% in the good enough category and in Cycle II it increased to 70% in the good category. In the evaluation aspect given by the tutor, the percentage score in Cycle I is 60% in the sufficient category, and it increased to 76% in Cycle II in the good category. Above all description, teachers’ competency can be increased through the implementation of KKG at SMP Negeri 6 Dumai.